An ethnographic study on the endorsement conference of the Department of Pediatrics, College of Medicine-Philippine General Hospital University of the Philippines Manila - Alinea, Ma. Cecilia D. (2003)
The Endorsement Conference is a teaching-learning strategy utilized by the Department of Pediatrics-Philippine General Hospital whereby the post duty team (senior and junior residents and medical students) updates the house staff of the present condition of endorsed critically-ill and newly admitted patients. Through the years, trainees noted that it has evolved in its structure and its target learners have become less participative, perceiving it as a less than valuable tool for learning. Due to this perception, an investigation into the dynamics behind the strategy was made. The main objective of this study was to provide a holistic picture of what the endorsement conference is like and how learning takes place in an objective, accurate and thorough manner. Using ethnography as study design, data collection procedures included documentation of actual goings-on in the thrice-a-week activity in a 2-month duration through a triangulation of audio and video tapes of the conference, collection of educational resources used, sociometry, flowcharting of direction and frequency of comments, focused group and individual interviews, and a semantic-differential rating-scale. The following areas were captured in the study: the physical environment, the intellectual and social atmosphere of the conference, how the conference rules were learned, modified and enforced, and the kinds of concerns the participants have of the activity. The study population included faculty members, fellows, residents and medical students (3rd to 5th year) who were the participants of the conference. Purposive sampling was employed for key participants and convenient sampling was used in focused group and individual interviews, and in the answering of the rating scale. Qualitative data analysis was used to triangulate and further analyze the data collected. Notes, records, and transcriptions were content analyzed, with focus on the recurring themes, intensity of how each theme was expressed, and patterns of verbal interaction among the participants using the Brown Interactive Analysis System (BIAS). Findings revealed that the endorsement conference was a traditional activity of the department, handed down from generation to generation and learned through experience as a student or a junior resident trainee. Aside from a general description of its schedule, participant roles and content flow in the annual report since 1996, the endorsement has not been documented in terms of its definition, objectives, general setup and implementation and evaluation. The conference was perceived to start early (7:30/ 8:00AM) and frequently conducted (thrice a week) with an average duration of one hours and 21 minutes at the Audio-Visual Room of the department. Its target learners included the whole house staff, with the senior members as facilitators and the post duty junior residents and medical students as presenters. The physical environment (A-V room) was perceived as well-lit, equipped with adequate sound system and other A-V equipment. The intellectual atmosphere was described in terms of the teaching-learning tools used by the participants such as facilitating and presenting. Facilitation was the primary teaching-learning tool used, and learning was noted to be facilitator-dependent due to the facilitator's ability to direct the conference being the rate-limiting step in task accomplishment. The presenters' preparedness in presenting and answering questions, though, were also contributory to achieving learning. All facilitators were perceived positively, with the chief resident being described as the most purposeful and informative. The first year residents as presenters were perceived to lack the mastery of presenting a more complete history and physical examination, while the medical students seemed to provide a more complete and relevant one, presenting clearly and in a lively manner, though tired due to their post-duty status. The social atmosphere, described in terms of the audience's interaction with all the participants, showed the audience being perceived as sleepy, preoccupied with other things, and passive as participants, though interested in the discussions. Its interaction with the presenter and amongst themselves were perceived as dynamic, open, friendly but somewhat serious. The presence of a hierarchy of authority was noted during endorsements, with the consultants high up in the totem pole. The endorsement conference was generally perceived as a valuable tool for learning despite its shortcomings in the technical aspect of its implementation. Thus, it was recommended that the department authorities reevaluate its present status, document its definition, objections, set-up and evaluation process, train the house staff on facilitation skills to maximize learning, and reorient them of conference's true nature and value.
Major project (Master in Health Professions Education)--University of the Philippines Manila
Keywords: Department of Pediatrics. Philippine General Hospital; Learning strategies; Endorsement Conference